A comparative study of automatic guidance signals and planting speeds for corn - Jarlyson Brunno Costa Souza; Bruna da Silva Brito Ribeiro; Edmilson Igor Bernardo Almeida; Andreza Maciel de Sousa; Aldair de Souza Medeiros; Washington da Silva Sousa (Acta Scientiarum. Agronomy, 2025)
Planting is considered one of the most critical mechanized agricultural operations, because any errors during this stage could cause significant yield losses. In this context, the use of automatic guidance systems can minimize errors in the row parallelism and alignment, ensuring consistent spacing and optimal operational speeds. Therefore, the objective of this study was to evaluate the effects of different GNSS correction signals and forward speeds on the corn planting. The treatments consisted in two GNSS correction signals for automatic guidance: SF1 – a free-to-use signal with ±23 cm pass-to-pass parallelism error, and SF2 – a subscription-based signal with ±5 cm pass-to-pass parallelism error; and three forward speeds (5, 6, and 8 km h-1). The depth and longitudinal seed distribution (classified as double, skipped, and acceptable spacings) were evaluated using statistical process control (SPC) and descriptive statistical methods. The results showed that the SF2 signal provided superior seeding quality, characterized by lower variability and enhanced process stability. Therefore, usage of the subscription-based SF2 signal is recommended to achieve optimal seeding quality. It improves the seed distribution and link to acceptable parallelism correction.